Guidance Note : Remote Learning and COVID-19 - World Bank (World Bank, Washington, DC, 2020)
Before the outbreak of the global novel coronavirus pandemic, the world was already dealing with a learning crisis, as evidenced by high levels of Learning Poverty. With the spread of the Coronavirus disease (COVID-19), among many disruptions to normal life, 160 countries have mandated temporary school closures, leaving ~1.6 billion children and youth out of school. Extended school closures may cause not only loss of learning in the short-term, but also further loss in human capital and diminished economic opportunities in the long-term. To help mitigate the loss of learning, many countries are pursuing options to utilize remote learning to manage and cope with the crisis. The World Bank is actively working with Ministries of Education in several countries to support their efforts in providing remote learning opportunities while schools are closed. This guidance note offers principles to maximize countries’ effectiveness in designing and executing remote learning.